3D freeze-printed cellulose-based aerogels: Obtaining truly 3D shapes, and functionalization with cross-linking and conductive additives. (August 2021) - Tetik, Halil; Zhao, Keren; Shah, Nasrullah; Lin, Dong
Abstract: Cellulose is the most abundant natural polymer existing on earth and nanomaterials derived from cellulose have been used in variety of applications. There is a great research interest in aerogels based on cellulosic nanomaterials due to their ultra-low thermal conductivity, modulus, sonic velocity, refractive index, dielectric constant, high specific surface area, and adjustable density. 3D printing of cellulose-based aerogels provided an ability to fabricate complex geometries with designed pore morphologies, which can be advantageous for various applications. Yet, the complexity of the geometry still has a limitation due to the lack of support material that can be removed from the structure without using harsh and tedious chemical / thermal processes that may affect the cellulosic material. In this study, by using water as support material, we have fabricated the first cellulose-based aerogels having truly 3D geometries with overhang features via the 3D freeze printing method incorporating a drop on demand-based materials deposition approach. The support material was removed from the main structure by a freeze-drying process, which is already a regular step in 3D printing process of aerogels. Fabricated aerogels possessed a highly ordered microstructure, in which the micropores were aligned along the freezing direction. We have investigated the effects of this anisotropy in the mechanical properties of the final aerogels. All the samples exhibited an excellent strain memory effect, and after 100 cyclic compression up to 25% strain, the obtained stress decay values were ~30% and ~16% in axial and radial directions, respectively. We further investigated the cross-linking of the fabricated aerogels to enhance their stability for making them feasible for applications such as biomedical or tissue engineering that requires wet environment. Finally, we functionalized the 3D printed cellulose-based aerogels with PEDOT:PSS, and evaluated their performance in piezoresistive sensing applications.